'What do I want to do with my life?' : a narrative analysis of women’s experiences approaching retirement following dedicated retirement planning : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, Albany, New Zealand - Southwick, Philippa Mary (Massey University, 2022)
The current cohort of women approaching retirement is large and includes a more diverse mix of personal and occupational situations than previous generations. Research on retirement planning has tended to focus the experiences of men and little is known about women’s experiences transitioning into retirement. Pre-retirement planning programmes are being increasingly promoted as a way to prepare for this transition. These planning programmes prompt people to imagine and prepare for life beyond paid employment. This provides an opportunity to explore how women plan for and anticipate retirement following attendance at a retirement planning workshop. This study explored how women anticipate retirement and the expectations shaping their retirement decisions. Semi-structured interviews were undertaken with ten women aged 50 and over who had all engaged in formal pre-retirement planning. The interviews enquired about their plans and expectations for retirement. The interviews were analysed using narrative analysis. Findings demonstrated that women resisted a version of retirement that is predicated on stereotypes of retirement as withdrawal from social life and gender norms of women as responsible for domestic and caring tasks. Three overarching narratives were described: ‘Marking Time’ in which women explored how they would fill their time in retirement; ‘One-way Door’ in which retirement was viewed as a new stage of life with implications for identity; and ‘Whose Retirement?’ in which women navigated their retirement plans as an individual or joint project. These narratives revealed the gendered nature of retirement planning and point to the societal expectations of retirement as an unsettling but also opportunistic time. Women expressed concerns about identity loss and missed opportunities once they retire and seek a retirement where they can remain productive and fulfilled. Their stories reflected the heterogenous nature of women’s experiences and the need for retirement planning that acknowledges this diversity. Such insights can inform workplace policy and practice around the development of pre-retirement planning to acknowledge the different expectations of retirement that women navigate.
Keywords: 520304 Health psychology